Adaptive Tracking Control Algorithm for Picking Wheel Robot - Zhiyong Zhang; Dongjian He (Institute of Advanced Engineering and Science, 2012)
The Objective of the paper is to investigate walking stability of picking wheel robot in the fields of medium speed and high load complex operating environment. Firsly, we analyze the influence on walking control for simplified dynamic model of picking robot and its remaining (instabilities), guarantee the stability and convergence of simplified system for tracking errors using the Lyapunov theory. Secondly, adaptive stabilization and tracking control algorithm is proposed on farmland in order to overcome its uncertainty and disturbances. Finally, the effectiveness and stability of the algorithm is verified using matlab simulation and experiment in the case of high load and medium speed. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1652